Efficacy and tolerability of sodium‐glucose co‐transporter‐2 inhibitors and glucagon‐like peptide‐1 receptor agonists: A systematic review and network meta‐analysis. Issue 7 (18th March 2020) - Hussein, Humaira; Zaccardi, Francesco; Khunti, Kamlesh; Davies, Melanie J.; Patsko, Emily; Dhalwani, Nafeesa N.; Kloecker, David E.; Ioannidou, Ekaterini; Gray, Laura J.
Abstract: Aim: To compare the efficacy and tolerability of sodium‐glucose co‐transporter 2 inhibitors (SGLT‐2is) and glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) in adults with type 2 diabetes. Materials and methods: Electronic databases were searched from inception to 24 April 2019 for randomized controlled trials reporting change in glycated haemoglobin (HbA1c) at approximately 24 and/or 52 weeks for SGLT‐2is and/or GLP‐1RAs (classified as short‐ and long‐acting). Bayesian network meta‐analyses were conducted to compare within and between SGLT‐2i and GLP‐1RA classes for cardiometabolic efficacy and adverse events (PROSPERO registration number: CRD42018091306). Results: Sixty‐four trials (53 trials of 24 weeks; seven trials of 52 weeks; four trials of both 24 and 52 weeks), comprising 31 384 participants were identified. Compared with placebo, all treatments improved HbA1c. Long‐acting GLP‐1RAs reduced HbA1c compared with short‐acting GLP‐1RAs and SGLT‐2is, with semaglutide showing greater reduction compared with placebo [24 weeks: −1.49% (95% credible interval: −1.76, −1.22); 52 weeks: −1.38% (−2.05, −0.71)] and all other treatments. Long‐acting GLP‐1RAs showed benefits in body weight and waist circumference reduction, while SGLT‐2is reduced blood pressure. SGLT‐2is showed increased risk of genital infection in comparison with long‐acting GLP‐1RAs [odds ratio (95% credible interval): 5.26 (1.45, 25.00)], while GLP‐1RAs showed increased risk of diarrhoea in comparison with SGLT‐2is [short‐acting GLP‐1RAs: 1.65 (1.09, 2.49); long‐acting GLP‐1RAs: 2.23 (1.51, 3.28)]. No other differences were found between SGLT‐2is and GLP‐1RAs in adverse events. Conclusion: Long‐acting GLP‐1RAs showed superiority in reducing HbA1c levels, body weight and waist circumference. SGLT‐2is showed reductions in blood pressure levels. This review provides essential evidence to guide treatment recommendations in the management of type 2 diabetes.